Scope project optimization on criteria income, time, cost, quality, risk - Кононенко, Игорь Владимирович; Колесник, Мария Эдуардовна (Eastern-European Journal of Enterprise Technologies, 2012)
A mathematical model of dynamic multi-objective optimization problem scope of the project with constraints and given alternative embodiments of the works presented in the form of network models is suggested